Profitability and Farmers Conservation Efforts on Sustainable Potato Farming in Wonosobo Regency - Liana Fatma Leslie Pratiwi; Suhatmini Hardyastuti; Lestari Rahayu Waluyati (Faculty of Agriculture, Universitas Gadjah Mada jointly with PISPI, 2016)
It takes into account in potato farming sustainability, since it was recognised as a holticultural commodity for farmers’ subsistence in Wonosobo Regency. For the reason that farming land was being degraded by errossion, the potato productivity apparently continued to decline. Potato farming sustainability can be deliberated from economic (profitability) and environmental (conservation efforts) points of view in order to remain profitable in a long term sustainable environment. This study is aimed to (1) to analyse the profitability of potato farming; (2) to analyse farmers’ effort on soil conservation and factors which affected sustainability of potato farming. The method used in this study was basic descriptive analysis. The study site was in Kejajar District, Wonosobo Regency, subsequently 50 random farmers as respondences was obtained. Gross Margin, Return on Invested Capital, and Operating Ratio were used to measure the profitability of potato farming. Conservation Activity Index (CAI) was used to measure farmers’ effort on soil conservation, while paired liner regression model with Ordinary Least Square (OLS) method was used to understand the factors which affected the conservation efforts of test sites. The study results revealed that the potato farming was profitable. Farmers conservation efforts mostly was in average category (74%), and only view in high category (16%) and low category (10%). Factors affected the farmers conservation efforts i.e. land area, potato products, potato price, the off-farm income, number of family members, farmers ages, and village dummy.